Searching for studies: A guide to information retrieval for Campbell systematic reviews - Heather MacDonald; Cozette Comer; Margaret Foster; Patrick R. Labelle; Scott Marsalis; Kate Nyhan; Zahra Premji; Morwenna Rogers; Ryan Splenda; Claire Stansfield; Sarah Young (Campbell Systematic Reviews, 2024)
Abstract This guide outlines general issues in searching for studies; describes the main sources of potential studies; and discusses how to plan the search process, design, and carry out search strategies, manage references found during the search process and document and report the search process.